2009
DOI: 10.1007/s11262-008-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Rana grylio virus thymidine kinase gene: an early gene of iridovirus encoding for a cytoplasmic protein

Abstract: The presence of thymidine kinase (TK) is a feature of many large DNA viruses. Here, a TK gene homologue was cloned and characterized from Rana grylio virus (RGV), a member of family Iridoviridae. RGV TK encodes a protein of 195 aa with a predicted molecular mass of 22.1 kDa. Homologues of the protein were present in all the currently sequenced iridoviruses, and phylogenetic analysis showed that it was much close to cellular TK type 2 (TK2), deoxycytidine kinase (dCK) and deoxyguanosine kinase (dGK). Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…RGV has been recognized as a member of the family Iridoviridae and is closely related to FV3, based on previous studies on morphogenesis, cellular interaction, antigenicity, restriction fragment length polymorphism (RFLP) and major capsid protein (MCP) sequence similarity [15][16][17][18]. To date, some genes of RGV have been identified and characterized, such as 3b-hydroxysteroid dehydrogenase (3b-HSD), deoxyuridine triphosphatase (dUTPase), an envelope protein gene (53R), thymidine kinase (TK) and a gene belonging to the ''essential for respiration and viability'' family (ERV1) [19][20][21][22][23][24]. We found that RGV could induce apoptosis mediated by mitochondria [25].…”
mentioning
confidence: 99%
“…RGV has been recognized as a member of the family Iridoviridae and is closely related to FV3, based on previous studies on morphogenesis, cellular interaction, antigenicity, restriction fragment length polymorphism (RFLP) and major capsid protein (MCP) sequence similarity [15][16][17][18]. To date, some genes of RGV have been identified and characterized, such as 3b-hydroxysteroid dehydrogenase (3b-HSD), deoxyuridine triphosphatase (dUTPase), an envelope protein gene (53R), thymidine kinase (TK) and a gene belonging to the ''essential for respiration and viability'' family (ERV1) [19][20][21][22][23][24]. We found that RGV could induce apoptosis mediated by mitochondria [25].…”
mentioning
confidence: 99%
“…The predicted proteins include DPOL, replication factor, NTPase/ helicase-like protein, RAD2 DNA repair protein, RNA polymerase subunits, and proteins involved in nucleic acid metabolism [5]. Although some of these proteins have been investigated [23][24][25][26][27][28][29], the detailed mechanisms of genome replication and transcription of ranaviruses remain largely an enigma. For example, the number of these potential proteins is still less than the number needed to complete the DNA replication and transcription cycles, and the predicted ones need to be proven experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular TKs, including cytosolic TK1 and mitochondrial TK2, are the key enzymes that catalyze the transfer of the γ-phosphate of ATP to 2′-deoxythymidine (dT) in the nucleoside salvage pathway, forming thymidine monophosphate (dTMP) in the presence of magnesium ions (Mg 2+ ). The vast majority of herpesviruses and some DNA viruses, such as vaccinia virus (VACV) (Deng et al., 2017), African swine fever virus (ASFV) (Sanford et al., 2016), and Rana grylio virus (RGV) (Zhao et al., 2009), also have a specific gene encoding a viral TK. For α-herpesviruses, but in particular for HSV-1, the expression of the viral TK is an important factor influencing virus characterization in acute and latent infection (Tenser et al., 1979; Huang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%